2019
DOI: 10.1101/709162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative plant-microbiome feedback limits productivity in aquaponics

Abstract: The demand for food will outpace productivity of conventional agriculture due to projected growth of the human population, concomitant with shrinkage of arable land, increasing scarcity of freshwater, and a rapidly changing climate. Efforts to increase conventional agricultural output come with significant environmental impacts stemming from deforestation and excessive use of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…group that, among the components of the system, was larger in the biofilter, while benzeneamine, N-ethyl- was negatively but not significantly ( p > 0.05) correlated with LAB, which were not quantified in this niche. In accordance with our results, Day et al [ 35 ] observed an accumulation of Pseudomonas in the biofilters of an aquaponic system during a cultivation cycle. The Pseudomonas spp.…”
Section: Resultssupporting
confidence: 94%
“…group that, among the components of the system, was larger in the biofilter, while benzeneamine, N-ethyl- was negatively but not significantly ( p > 0.05) correlated with LAB, which were not quantified in this niche. In accordance with our results, Day et al [ 35 ] observed an accumulation of Pseudomonas in the biofilters of an aquaponic system during a cultivation cycle. The Pseudomonas spp.…”
Section: Resultssupporting
confidence: 94%
“…Among NOBs, Nitrospira and Nitrobacter were found in all plots. Nitrifying bacteria including Nitrosomonas, Nitrobacter, and Nitrospira are commercially used for initiating nitrogen cycling and promoting plant growth [35][36][37]. These bacteria seemed to play important roles in the tanks of AP and AC.…”
Section: Discussionmentioning
confidence: 99%